Efektifitas Manajemen Keuangan UMKM di Kota Palangka Raya Sebagai Strategi pada Masa New Normal Covid-19 - Dicky Perwira Ompusunggu; Melya Nanda (Jurnal Visi Manajemen, 2023)
This journal discusses the effectiveness of financial management in Micro, Small and Medium Enterprises (MSMEs) in Palangka Raya City as a strategy in dealing with the New Normal period of COVID-19. The purpose of this research is to find out how MSMEs in Palangka Raya City manage their finances during the pandemic and how it affects their business performance. The method used in this study was direct interviews with 3 respondents consisting of MSME owners and their financial managers. The results of the study show that MSMEs in Palangka Raya City apply various financial management strategies such as cost savings and increased efficiency in their business processes. In facing the New Normal period of COVID-19, effective financial management can help MSMEs to continue operating and even improve their business performance. In conclusion, effective financial management is a key factor in maintaining the survival of MSMEs during this pandemic.